2006
DOI: 10.1504/ijram.2006.009548
|View full text |Cite
|
Sign up to set email alerts
|

Potential for arsenic contamination of rice in Bangladesh: spatial analysis and mapping of high risk areas

Abstract: Knowledge of the location and severity of arsenic contamination in Bangladesh is required to develop land and resource management strategies to reduce both human exposure to arsenic and arsenic contamination of food and water supplies. While the threat posed by directly drinking arsenic contaminated water has been well documented, the potential for exposure through secondary sources is not as well-understood. Given that rice accounts for 70% of an average adult's caloric intake in Bangladesh, the potential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Of the three rice seasons, Boro (dry season rice) is fully grown under irrigated condition and 79.1% of the Boro area is irrigated by ground water [10] and, thus, growing rice in the Boro season has become the major concern in terms of arsenic poisoning in human body. Ross et al [11] reported that mean ground water arsenic concentrations are below 50  μ g/L in 76% of irrigated Boro rice areas and in 7% of areas, mean concentrations of As are greater than 100  μ g/L primarily in south central and western central Bangladesh. Arsenic in rice grains is especially dangerous for the Bangladeshi people because of the relatively high consumption of about 450 g per person per day.…”
Section: Introductionmentioning
confidence: 99%
“…Of the three rice seasons, Boro (dry season rice) is fully grown under irrigated condition and 79.1% of the Boro area is irrigated by ground water [10] and, thus, growing rice in the Boro season has become the major concern in terms of arsenic poisoning in human body. Ross et al [11] reported that mean ground water arsenic concentrations are below 50  μ g/L in 76% of irrigated Boro rice areas and in 7% of areas, mean concentrations of As are greater than 100  μ g/L primarily in south central and western central Bangladesh. Arsenic in rice grains is especially dangerous for the Bangladeshi people because of the relatively high consumption of about 450 g per person per day.…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than 400 plant species have been reported as major soil contaminant, metal hyperaccumulators, representing less than 0.2% of all angiosperms (Ross et al, 2006;Yang et al, 2013). Promising studies at molecular level shows that the major soil contaminant in our dying industrial area of our country, Zinc (Zn) uptake is regulated by ZIP family genes in Arabidopsis thaliana (Shahandeh and Hossner, 2000;Haque et al, 2016).…”
Section: Molecular Studies Related To Phytoremediationmentioning
confidence: 99%
“…There is a growing trend in areas of land, surface waters and groundwater around the world affected by contamination from industrial and agricultural activities either due to ignorance, lack of vision, or carelessness (Hauqe et al, 2016;Ross et al, 2006;Yang et al, 2013). For example, concentrations of Cu, Zn, Pb, Cr, Cd, Fe, and Ni estimated in soils and vegetables grown in and around an industrial area of a developing country, Bangladesh showed the following order of metal contents in contaminated irrigation water: Fe >Cu>Zn>Cr>Pb>Ni>Cd.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations